An Analysis of Metaphor in Politics Articles in The Jakarta Post Online Newspaper During Pandemic Covid-19 Era - chandri febri santi; Ulfatmi Azlan; dara dinanti (English Language, Linguistics, Literature, And Education Journal, 2022)
This research discusses metaphor used in politics articles in the Jakarta Post online newspaper during pandemic covid-19 era. The aim of this research is to find the kind of metaphor and conceptual meaning of metaphor. The methodology used in this research is descriptive qualitative method. Sources of data iin ithis istudy iare iarticles iin i iThe iJakarta iPost ionline inewspaper, iespecially ipolitical iarticles. iData icollection iwas icarried out iby itaking iseveral iarticles ion iPolitics iin ithe iCovid-19 iPandemic iEra. This research using George Lakoof and Mark Jhonson theory for analyze kinds of metaphors, while analyzing the meaning of metaphor using Zoltan Covesces theory. The result of this research is 25 data containing all kinds of metaphor which are five data of orientational metaphor, five data of ontological metaphor, and fifteen data of structural metaphor. The meaning of metaphor is conceptual meaning, namely interpreting imetaphors iusing ithe isource iand itarget idomains, whie the most dominant metaphor is structural metaphors.